Parameters of water consumption associated with the microclimate of an orchard of jaboticaba trees in southern Brazil - Bergamaschi, Homero; Prua, Cristiano Knevitz (Agrometeoros, 2018)
This work aimed to quantify the evapotranspiration and to evaluate the microclimate of an orchard of jaboticaba trees [Plinia peruviana (Poir.) Govaerts]. Field studies were carried out in Porto Alegre, RS, in humid subtropical climate. The orchard was implanted in 2005, with plant spacing of 4.5m x 4.5m. Air temperature and relative humidity, photosynthetically active radiation (PAR), inside and outside the canopy, and soil moisture were monitored continuously. The evapotranspiration of the crop (ETc) was calculated by the decrease of the soil-water storage. The ETc/ETo ratio was determined by linear regression analysis, with ETo being the reference evapotranspiration. The relative humidity was higher inside than outside the canopy, with similar trend in air temperature. The interception efficiency of PAR increased from 80% in autumn-winter to 92% in spring-summer. ETc followed evaporative demand and leaf area, ranging from 0.3 to 3.2 mm day-1 in winter and from 0.2 to 5.0 mm day-1 in the summer. Most of the soil-water extraction occurred between 0 and 40 cm depth. The ETc/ETo ratio (assumed as Kc coefficient) was 0.95, ranging from 0.90 in winter to 1.06 in summer. Regression analyzes were effective in determining the ETc/ETm ratio, with better performance at high evaporative demand.